2019
DOI: 10.1134/s2517751619040085
|View full text |Cite
|
Sign up to set email alerts
|

Pervaporation Desulfurization of a Thiophene/n-Octane Mixture Using PPO Membranes Modified with Hybrid Star-Shaped Macromolecules

Abstract: The presence of sulfur-containing impurities in petroleum naphtha causes a decrease in the cost and quality of fuels, a reduction in the service life of car engines, and an increase in the amount of harmful emissions into the atmosphere. Pervaporation is an alternative cost-effective fuel desulfurization method. In this study, hybrid membranes based on poly(2,6-dimethyl-1,4-phenylene oxide) and a star-shaped modifier for the pervaporation separation of a thiophene/n-octane model mixture is developed. Hybrid st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Hybrid PPO membranes modified with star macromolecules composed of a C 60 core and six polystyrene (PS) arms and six poly-2-vinylpyridine (P2VP) arms have provided enhanced selectivity in dehydration of acetic acid [26] and separation of the quaternary mixture (n-propanol/acetic acid/propyl acetate/water) [27]. It has been reported [27][28][29][30][31] that PPO membranes modified with star macromolecules exhibited enhanced pervaporation performance, presumably due to the presence of polymer arms with a different chemical nature (nonpolar and polar) in a modifier. The PS arms are fully compatible with the PPO matrix and a phase separation does not occur up to the temperatures of their thermal destruction [32].…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid PPO membranes modified with star macromolecules composed of a C 60 core and six polystyrene (PS) arms and six poly-2-vinylpyridine (P2VP) arms have provided enhanced selectivity in dehydration of acetic acid [26] and separation of the quaternary mixture (n-propanol/acetic acid/propyl acetate/water) [27]. It has been reported [27][28][29][30][31] that PPO membranes modified with star macromolecules exhibited enhanced pervaporation performance, presumably due to the presence of polymer arms with a different chemical nature (nonpolar and polar) in a modifier. The PS arms are fully compatible with the PPO matrix and a phase separation does not occur up to the temperatures of their thermal destruction [32].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the study of the transport parameters of the membranes in pervaporation of the thiophene/n-heptane mixture showed that the PEA membrane is more selective for the isolation of thiophene impurities, although the polymer-metal complex exhibits a higher total flux. The membranes under study demonstrate moderate separation properties over those of the literature data [15][16][17][18]21]; however, they are very thermally and mechanically strong and show long-term operational stability.…”
Section: Pervaporation Of Thiophene/n-heptane Mixturementioning
confidence: 79%
“…The main sulfur-containing impurity in hydrocarbons extracted from the Earth is thiophene; therefore, in this work, a model gasoline consisting of a binary mixture of thiophene and n-heptane is considered. As membrane material for removal of thiophene from gasoline, different polymers such as polyphenylene oxide, polyphosphazene, polyvinylidene fluoride, polyhedral oligomeric silsesquioxane POSS, polysulfone, and polyether-block-amide Pebax, have been used [15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Hyder and Chen provided another method for PVA modification that consisted of mixing a polymer solution with different amounts of chitosan (CS) (25,50,70,75, and 80 wt.%) [30]. It is known that successful mixing can improve separation characteristics, since the mobility of macromolecular chains changes in the process of intermolecular interactions between polymers.…”
Section: Poly(vinyl) Alcoholmentioning
confidence: 99%
“…Introducing star-shaped macromolecules as fillers can be a promising way to improve the separation capacity of pervaporation membranes [ 73 , 74 , 75 ]. Hybrid membranes based on poly(2,6-dimethyl-1,4-phenylene oxide) (PPO) modified with heteroarm stars (HAS) ( Figure 3 ) were developed by Rostovtseva et al [ 76 ].…”
Section: Membranes For Eg Dehydrationmentioning
confidence: 99%